2021
DOI: 10.3390/jcm10112253
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation and Physical Performance in Patients after Myocardial Infarction: Preliminary Research

Abstract: (1) Background: Cardiovascular diseases, in particular, myocardial infarction (MI), are the main threats to human health in modern times. Cardiac rehabilitation (CR), and especially increased physical activity, significantly prevent the consequences of MI. The aim of this study was to assess physical performance in patients after MI before and after CR. (2) Methods: 126 patients after MI were examined. They were admitted to the cardiac rehabilitation ward twice: in the 3rd month after MI, and then in the 6th m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Our findings indicated that the CSC-Infarct can improve symptoms, functional capacity, and health-related quality of life in MI patients. These benefits are associated with faster recovery in MI patients compared to groups that enter the second stage of CR later than the average of 10 days after MI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings indicated that the CSC-Infarct can improve symptoms, functional capacity, and health-related quality of life in MI patients. These benefits are associated with faster recovery in MI patients compared to groups that enter the second stage of CR later than the average of 10 days after MI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPr shows how the heart is coping with a given exercise and how much work it took to overcome the given load on a treadmill. The DPr may also be of great prognostic value in the assessment of cardiovascular function in healthy people with different fitness levels [ 29 ]. Our research revealed that the resting index based on DPr increased after the 4-weeks CSC-Infarct rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adult mammalian heart is limited to repair after injury, and the lost cells are replaced by a fibrotic scar, which results in cardiac dysfunction. Exercise training has been proven to be an effective strategy of rehabilitation for MI patients [11,12]. Some studies detected the cardioprotective effects of different types of exercise models [6,7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Ameliorating cardiac fibrosis and inhibiting cardiomyocytes apoptosis would be key therapeutic targets to improve cardiac function following MI. Increasing data from clinic and animal research suggests that exercise training is an effective strategy in improving cardiac function [6][7][8][9][10][11][12]. Exercise training has beneficial effects on preventing or reversing pathological cardiac remodeling by reducing collagen production [13].…”
Section: Introductionmentioning
confidence: 99%